Altra IQ Smart Shoes / Nur Liyana Ishak - Ishak, Nur Liyana; Ismail, Nur Damia Auni; Ismail, Umi Nasuha; Hazaha’AR, NuR Haziqah; Mohd Subardi, Siti Nur Aishah; Ahmad, Siti Misliah (2021)
In the information technology (Hons)subject the theoretical part of the topic was the paper. The main objective was to familiarise students with the practical use of the company. This study learned about the factors that helped to launch a new product. A general introduction to the new product development took place in the first phase of the report. In this part, an analysis of methodology and limitations were explained about the problem faced by a user when doing outdoor activities. During the next phase of the report, this report also mentioned the definition, classification and process of the new product development. Improvements and product revisions are the classification of the new product. In addition, five processes, including research and development, product design/features, concept testing, a prototype design and finally testing marketing, can be divided on the process for new product development. Furthermore, the concept testing and market research conducted in Google Form with questionnaires. Finally, several techniques were used in test marketing to make this product acceptable to the community, such as the experience of customers, starting with opinions and feedback. To conclude, the public feedback was very helpful in meeting the consumer's demand and in flowing the trend time. In short, the development of a new product is Altra IQ Smart Shoes falling into a new product to the company. this start, an idea generation solution in Samsung company known for its electronic product. The design level and features of the product are specified in terms of performance, reliability, safety in use, durability and uniqueness. Next, a successful prototype for Altra IQ smart Shoes that showcases its unique design and features. In conclusion, public feedback is very helpful in meeting consumer demand and flowing trend times.